Numerical analysis of the stress state of a spherical contact system with an interlayer of antifriction material - Kamenskih, Anna Aleksandrovna; Trufanov, Nikolay Aleksandrovich (Computational Continuum Mechanics, 2013)
The stress-strain state of a spherical contact system with an interlayer of antifriction polymeric material is studied by considering the elastic-plastic contact problem and taking into account contact surface friction. The finite-element method is used to explore the deformation behavior of samples made of three different antifriction polymeric materials. Numerical results are found to be in good quantitative agreement with experimental results. The problem of mechanical interactions in the system with complex geometry is formulated for axisymmetric and three-dimensional cases. By solving the axisymmetric problem, contact characteristics are investigated using different finite element meshes. Mesh parameters are determined for a three-dimensional model. Numerical analysis shows the effect the system geometry on the distribution of contact zones (adhesion, slipping and detachment), and the value and character of contact pressure and tangential stress.
Keywords: contact problem; finite element method; friction; spherical contact system; antifriction polymeric interlayer